Extracellular miRNAs: From Biomarkers to Mediators of Physiology and Disease - Mori, Marcelo A.; Ludwig, Raissa G.; Garcia-Martin, Ruben; Brandão, Bruna B.; Kahn, C. Ronald (Cell metabolism, 2019)
miRNAs can be found in serum and other body fluids and serve as biomarkers for disease. More importantly, secreted miRNAs, especially those in extracellular vesicles (EVs) such as exosomes, may mediate paracrine and endocrine communication between different tissues and thus modulate gene expression and the function of distal cells. When impaired, these processes can lead to tissue dysfunction, aging, and disease. Adipose tissue is an especially important contributor to the pool of circulating exosomal miRNAs. As a result, alterations in adipose tissue mass or function, which occur in many metabolic conditions, can lead to changes in circulating miRNAs, which then function systemically. Here we review the findings that led to these conclusions and discuss how this sets the stage for new lines of investigation in which extracellular miRNAs are recognized as important mediators of intercellular communication and potential candidates for therapy of disease.